Use of Stress Testing and Diagnostic Catheterization after Coronary Stenting: Association of Site-level Patterns with Patient Characteristics and Outcomes in 247,052 Medicare Beneficiaries - Shah, Bimal R. (2013)
OBJECTIVES: To determine diagnostic testing patterns after percutaneous coronary intervention (PCI). BACKGROUND: Little is known about patterns of diagnostic testing after PCI in the U.S. or the relationship of these patterns with clinical outcomes. METHODS: We linked Centers for Medicare & Medicaid Services inpatient and outpatient claims to the National Cardiovascular Data Registry(®) CathPCI Registry(®) data from 2005–2007. Hospital quartiles of the cumulative incidence of diagnostic testing use within 12 and 24 months post-PCI were compared for patient characteristics, repeat revascularization, acute myocardial infarction (AMI), and death. RESULTS: A total of 247,052 patients underwent PCI at 656 institutions. Patient and site characteristics were similar across testing use quartiles. There was a 9% and 20% higher adjusted risk of repeat revascularization in Quartile 3 and Quartile 4 (highest testing rate), respectively, when compared to Quartile 1 (lowest testing rate) (p=0.020 and <0.0001, respectively). The adjusted risk for death or AMI did not differ among quartiles. CONCLUSIONS: While patient characteristics were largely independent of rates of post-PCI testing, higher testing rates was not associated with lower risks of myocardial infarction or death, but repeat revascularization was significantly higher at these sites. Additional studies should examine whether increased testing is a marker for improved quality of post-PCI care or simply increased healthcare utilization.